Increased levels of PD‐1 expression on CD8 T cells in patients post‐renal transplant irrespective of chronic high EBV viral load. (30th September 2013) - Moran, Julie; Dean, Jonathan; De Oliveira, Andre; O'Connell, Marie; Riordan, Michael; Connell, Jeff; Awan, Atif; Hall, William W.; Hassan, Jaythoon
Abstract: Studies have identified solid organ transplant recipients who remain asymptomatic despite maintaining CHL. Factors which determine the CHL state remain poorly understood but are likely to involve immunological control of the viral infection. We monitored expression of PD‐1, a marker of T‐cell exhaustion and viral persistence, on CD8 T cells in patients who resolved EBV infection as determined by undetectable EBV DNA (REI) and CHL patients. PD‐1 expression on CD8 T cells was increased in the first year post‐transplant irrespective of EBV outcome, and most CD8 T cells continued to express PD‐1 for up to three yr post‐transplant. Although all patient groups showed similar frequencies of EBV‐specific CD8+ T cells, PD‐1 expression on these cells increased in the post‐transplant groups compared with the pretransplant patients. Functional studies of EBV‐specific CD8+ T cells stimulated with BZLF or LMP2 peptide pools revealed monofunctional IFN‐γ responses. Our results indicate that PD‐1 expression on CD8 T cells post‐transplant may result from factors other than antigenic stimulation.